Osteopontin, CCL5 and CXCL9 are independently associated with psoriasis, regardless of the presence of obesity. Issue 2 (August 2015) - Duarte, G.V.; Boeira, V.; Correia, T.; Porto-Silva, L.; Cardoso, T.; Macedo, M.N.; Oliveira, M.F.; Carvalho, E.
Highlights OPN, CCL5 and CXCL9 levels are higher in psoriasis patients than controls, regardless of obesity. OPN plasma levels are highly (OR = 19.25) associated with occurrence of psoriasis. CCL2 levels are higher in obese than non-obese psoriasis patients. Facial involvement and PASI are not associated to OPN, CCL5, CCL2 or CXCL9 elevation. No correlation was found between OPN and CXCL9 as well as between OPN and TNF.